Pengaruh Core Self Evaluations dan Gaya Kepemimpinan Terhadap Kinerja Auditor (Pada Badan Pemeriksa Keuangan Republik Indonesia Perwakilan Provinsi Riau) - Agustiawan Agustiawan; Ari Irawan; Rama Gita Suci (Politeknik Negeri Bengkalis, 2020)
The purpose of this study is to examine the effect of core self evaluations and leadership styles on auditor performance. The population were auditors who worked in Indonesia Supreme Audit Institution, Riau Province branch, with as many as 64 auditors. This study is a population study, so the sample consisted of 64 auditors. The data used are primary data, which was done by using survey methods with questionnaire techniques. The data processing method used is multiple linear regression. Based on the results, it can be concluded that locus of control, emotional stability, self esteem, self efficacy and leadership style variables influence auditor performanceÂ Keywords: Locus of control, emotional stability, self esteem, self efficacy, leadership styleÂ Â and auditor performance.